NKT associated Hedgehog and Osteopontin drive fibrogenesis in nonalcoholic fatty liver disease - Syn, Wing-Kin (2012)
Immune responses are important in dictating nonalcoholic steatohepatitis (NASH) outcome. We previously reported that upregulation of hedgehog (Hh) and osteopontin (OPN) occurs in NASH, that Hh-regulated accumulation of natural killer T (NKT) cells promotes hepatic stellate cell (HSC) activation, and that cirrhotic livers harbor large numbers of NKT cells. Here, we evaluated the hypothesis that activated NKT cells drive fibrogenesis during NASH by assessing if NKT depletion protects against NASH-fibrosis; identifying the NKT associated fibrogenic factors; and correlating plasma levels of the NKT cell-associated factor OPN with fibrosis severity in mice and humans. When fed methionine choline deficient (MCD) diets for 8 weeks, WT mice exhibited Hh pathway activation, enhanced OPN expression, and NASH-fibrosis. Jα18−/− and CD1d−/− mice which lack NKT cells had significantly attenuated Hh and OPN expression and dramatically less fibrosis. Liver mononuclear cells (LMNC) from MCD diet-fed WT mice contained activated NKT cells, generated Hh and OPN, and stimulated hepatic stellate cells (HSC) to become myofibroblasts (MF); neutralizing these factors abrogated the fibrogenic actions of WT LMNC. LMNC from NKT cell deficient mice were deficient in fibrogenic factors, failing to activate collagen gene expression in HSC. Human NASH livers with advanced fibrosis contained more OPN and Hh protein than those with early fibrosis. Plasma levels of OPN mirrored hepatic OPN expression, and correlated with fibrosis severity. In conclusion, hepatic NKT cells drive production of OPN and Hh ligands that promote fibrogenesis during NASH. Associated increases in plasma levels of OPN may provide a biomarker of NASH-fibrosis.